Blockade of AMPK-Mediated cAMP–PKA–CREB/ATF1 Signaling Synergizes with Aspirin to Inhibit Hepatocellular Carcinoma - Zhang, Hongying (Cancers (Basel), 2021)
SIMPLE SUMMARY: Epidemiological and experimental studies have demonstrated that aspirin (acetylsalicylic acid) may prevent the incidence of some types of human cancer, including colorectal cancer and hepatocellular carcinoma (HCC). In addition, preclinical studies indicate that aspirin in combination with other treatments may achieve a more significant anti-cancer effect for established tumors. This study aims to improve the anti-cancer effect of aspirin by targeting signaling pathways related to aspirin and its targets. We find that aspirin may induce cAMP–PKA–CREB/ATF1 signaling in HCC via AMPK and its downstream target carbamoyl-phosphate synthase 1 (CPS1). Blockade of PKA–CREB/ATF1 signaling by the natural agent berbamine could sensitize HCC to aspirin. This research indicates that the combination of two inexpensive drugs, aspirin and berbamine, holds promise in preventing and treating HCC. ABSTRACT: Aspirin can prevent or inhibit inflammation-related cancers, such as colorectal cancer and hepatocellular carcinoma (HCC). However, the effectiveness of chemotherapy may be compromised by activating oncogenic pathways in cancer cells. Elucidation of such chemoresistance mechanisms is crucial to developing novel strategies to maximize the anti-cancer effects of aspirin. Here, we report that aspirin markedly induces CREB/ATF1 phosphorylation in HCC cells, which compromises aspirin’s anti-HCC effect. Inhibition of AMP-activated protein kinase (AMPK) abrogates the induction of CREB/ATF1 phosphorylation by aspirin. Mechanistically, activation of AMPK by aspirin results in decreased expression of the urea cycle enzyme carbamoyl-phosphate synthase 1 (CPS1) in HCC cells and xenografts. Treatment with aspirin or CPS1 knockdown stimulates soluble adenylyl cyclase expression, thereby increasing cyclic AMP (cAMP) synthesis and stimulating PKA–CREB/ATF1 signaling. Importantly, abrogation of aspirin-induced CREB/ATF1 phosphorylation could sensitize HCC to aspirin. The bis-benzylisoquinoline alkaloid berbamine suppresses the expression of cancerous inhibitor of protein phosphatase 2A (CIP2A), leading to protein phosphatase 2A-mediated downregulation of CREB/ATF1 phosphorylation. The combination of berbamine and aspirin significantly inhibits HCC in vitro and in vivo. These data demonstrate that the regulation of cAMP-PKA-CREB/ATF1 signaling represents a noncanonical function of CPS1. Targeting the PKA–CREB/ATF1 axis may be a strategy to improve the therapeutic effects of aspirin on HCC.